Edad del trasplante y su influencia en las características agronómicas y rendimiento en Apium graveolens L. “apio”, Zungarococha - Loreto.2019 - Cruzalegui Teco, Zoila Rosa (Universidad Nacional de la Amazonía Peruana, 2022)
The research was carried out in the Workshop of Teaching and Research of Horticultural Plants (TEIPH), of the Faculty of Agronomy-UNAP, located at Km. 3 of the road to Quistococha-LLanchama, located south of the city of Iquitos, presenting the following coordinates in UTM: 9576237 North and 682157 South and the Altitude of 126 meters above sea level. The type of research was experimental, explanatory with an independent variable (transplant age) and nine dependent variables (plant height, stem length, stem diameter, root length, plant diameter, number of petioles/plant, total plant weight, petiole/plant weight and petiole/ha weight); the objective of the research work was to determine the influence of the transplant age on the agronomic characteristics and performance of Apium graveolens L. "celery", Zungarococha-Loreto. The experimental design used was the Completely Random Block Design, with four treatments and four repetitions. Each experimental unit consisted of 3 rows, 8 plants/row and the sampling unit consisted of four plants/experimental unit. The transplant age in Apium graveolens L, "celery", if it significantly influences the agronomic characteristics and yield of the crop. T4 treatment (105 days) as the average transplant age exhibited the best agronomic characteristics and crop yield. The highest floor height, stem length and diameter, root length, diameter and number of petioles/plant, was the T4 Treatment (105 days). The total weight yields, petiole/plant weight and petiole/ha weight, was achieved by T4 (105 days). Treatment T4 (105 days) presented the best weight performance of petioles/ha with 5,325 t/ha, followed by T3 (75 days) with 3,636 t/ha; then the T2 (60 days) with 2.417 t/ha and finally the T1 (90 days) with 1,650 t/ha.

La investigación se llevó a cabo en el Taller de Enseñanza e Investigación de Plantas Hortícolas (TEIPH), de la Facultad de Agronomía-UNAP, ubicada en el Km. 3 de la carretera a Quistococha-LLanchama, situada al Sur de la ciudad de Iquitos, presentando las siguientes coordenadas en UTM: 9576237 Norte y 682157 Sur y la Altitud de 126 msnm. El tipo de investigación fue experimental, explicativo con una variable independiente (edad del trasplante) y nueve variables dependientes (altura de planta, longitud del tallo, diámetro de tallo, longitud de la raíz, diámetro de la planta, numero de peciolos/planta, peso total de la planta, peso de peciolos/planta y peso de peciolos/ha); el objetivo del trabajo de investigación fue determinar la influencia de la edad del trasplante en las características agronómicas y rendimiento de Apium graveolens L. “apio”, Zungarococha-Loreto. El Diseño experimental que se utilizo fue el Diseño de Bloques Completamente al Azar, con cuatro tratamientos y cuatro repeticiones. Cada unidad experimental estuvo constituida de 3 filas, 8 plantas/fila y la unidad de muestreo estuvo constituida por cuatro plantas/unidad experimental. La edad del trasplante en Apium graveolens L,”apio”, si influye significativamente en las características agronómicas y rendimiento del cultivo. El Tratamiento T4 (105 días) como edad promedio del trasplante presentó las mejores características agronómicas y rendimiento del cultivo. La mayor altura de planta, longitud y diámetro del tallo, longitud de la raíz, diámetro y número de peciolos/planta, lo tuvo el Tratamiento T4 (105 días). Los rendimientos de peso total, peso de peciolos/planta y peso de peciolos/ha, lo tuvo el T4 (105 días). El tratamiento T4 (105 días), presentó el mejor rendimiento de peso de peciolos/ha, con 5.325 t/ha, seguido del T3 (75 días) con 3.636 t/ha; luego, el T2 (60 días), con 2.417 t/ha y finalmente el T1 (90 días) con 1.650 t/ha.
Keywords: Transplante; Apio; Apium graveolens; Características agronómicas; Rendimiento de cultivos; https://purl.org/pe-repo/ocde/ford#4.01.06